1995
DOI: 10.1002/mc.2940140409
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of ki‐ras amplification and p53 gene mutations in adenocarcinomas of the human esophagus

Abstract: Mutated ras genes have been found to be conspicuously absent from primary tumors of the esophagus, although high expression of ras p21 oncoprotein in some esophageal squamous cell carcinomas and mutations of the Ki- and Ha-ras genes in esophageal carcinoma cell lines have been reported. In this study, we found amplification of the Ki-ras gene in four of 10 esophageal adenocarcinomas (40%). No such amplification was observed among 61 squamous cell carcinomas, one pseudosarcomatous carcinoma, and eight esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 18 publications
0
21
0
4
Order By: Relevance
“…Activated Ha-ras, seen in BPV-4 associated carcinoma, was required for immortalization of BPV-4-transformed cells, due to the lack of the E6 gene in BPV-4 (Jackson et al, 1991). Members of the ras gene family are often overexpressed or amplified (Sorsdahl et al, 1994;Galiana et al, 1995) in human oesophageal cancers, implicating the ras proteins in oesophageal carcinogenesis, although activating point mutations are rare (Casson et al, 1997;Arber et al, 2000). It would be informative to ascertain what effects quercetin would have in HFKE6/E7 overexpressing ras.…”
Section: Waf1mentioning
confidence: 99%
“…Activated Ha-ras, seen in BPV-4 associated carcinoma, was required for immortalization of BPV-4-transformed cells, due to the lack of the E6 gene in BPV-4 (Jackson et al, 1991). Members of the ras gene family are often overexpressed or amplified (Sorsdahl et al, 1994;Galiana et al, 1995) in human oesophageal cancers, implicating the ras proteins in oesophageal carcinogenesis, although activating point mutations are rare (Casson et al, 1997;Arber et al, 2000). It would be informative to ascertain what effects quercetin would have in HFKE6/E7 overexpressing ras.…”
Section: Waf1mentioning
confidence: 99%
“…However, activation of K-ras oncogene is not exclusively associated with K-ras mutation. Studies have shown that in the absence of activating mutations, K-ras may still play a role in oncogenesis via Ras gene amplification, overexpression or upstream activation of the pathway (10)(11)(12)(13) In our previous studies, we employed the microarray technique combined with bioinformatics tools to screen all differentially expressed genes after activated K-ras oncogene in human adrenocortical cells transfected with a K-ras mutant, and determined 22 potential gene targets. Then, a membrane array blotted with these 22 gene probes was constructed and applied to test the peripheral blood samples from patients with various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, on average, 45% of esophageal carcinomas contain p53 mutations (Greenblatt et al, 1994); however, this frequency can vary in China from 20% to 55% depending on the province or region in which the patients live (Lung et al, 1996). In addition, p53 mutations are found more frequently in esophageal adenocarcinoma than in esophageal squamous-cell carcinoma (SCC) (Galiana et al, 1995;Gleeson et al, 1995;Liang et al, 1995). GC = AT transitions are the predominant class of mutation detected in the p53 gene of esophageal tumors, though exceptions have been found (Liang et al, 1995).…”
mentioning
confidence: 99%